Group differences in social inclusion between young adults aged 18 to 25 with serious mental illness and same-aged peers from the general community. (November 2019) - Gardner, Andrew; Cotton, Sue; O'Donoghue, Brian; Killackey, Eóin; Norton, Peter; Filia, Kate
Aims: Young adults with serious mental illness (SMI) are thought to be socially excluded. However, psychometric measures of social inclusion have not been employed to examine group differences relative to peers from the general community. The aim of this study was to employ such a measure to determine differences in social inclusion between young adults with SMI and peers from the general community. Methods: A cross-sectional hierarchical logistic regression was conducted to identify which dimensions and individual indicators from the Filia Social Inclusion Measure (F-SIM) discriminated between n = 152 young adults aged 18–25 from the general community ( M = 21.36, SD = 2.16) and n = 159 young adults aged 18–25 with SMI ( M = 21.13, SD = 2.21). Results: Group membership was accounted for by Interpersonal Connections (Nagelkerke R 2 = .32), Vocational & Financial Security (Nagelkerke R 2 = .32) and Healthy Independent Lifestyle (Nagelkerke R 2 = .08) dimensions of the F-SIM. Relative to young adults from the general community, those with SMI were five times less likely to feel they had friends who would call on them in a crisis, odds ratio (OR) = .19 (95%CI = .04, .53), p = .04, almost five times more likely to live with their parents, OR = 4.79 (95%CI = 1.98, 11.15), p = .004, almost four times less likely to have worked/studied any time over the past 12 months, OR = .27 (95%CI = .11, .64), p < .001, and three-and-a-half times more likely to report unstable accommodation, OR = 3.58 (95%CI = 1.14, 11.15), p = .03. Conclusion: Young adults with SMI are socially excluded relative to peers from the general community in terms of interpersonal connections, vocational engagement, autonomy/independence and housing stability. In addition to the well-established focus on vocational engagement, interventions to improve social inclusion in this population must promote reciprocity within social relationships and healthy autonomy/independence (including stable housing).